Comparative Study of Hisbah Institutions and Consumer Protection Institutions In Indonesia In A Review of Islamic Business Ethics - Ananto Triwibowo; Dimas Pratomo; Nur Sya'adi; Muhammad Afani Adam (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2022)
Islam does not teach people to be concerned with the world or the events of the afterlife, but both must be in harmony. Islam not only gives its followers the freedom to do business, but it also provides some basic principles for doing business: unity, balance, free will, responsibility, and truth, including virtue and honesty. The Hisba is a government-controlled religious organization that oversees the proper fulfillment of its obligations by the community when society begins to neglect its obligations, and when people become accustomed to this error, society does wrong. Its general purpose is to protect the communal environment from harm, preserve its existing destiny, and ensure the well-being of the community, both in terms of religion and daily conduct, according to divine law